Attention: The Cognitive Effects of Learning to Read in Arabic by Chinese Learners at an Old Age - Hong Liu (SAGE Open, 2023)
This paper presents the results of a retrospective study that investigates the cognitive effects of learning a foreign language in late adulthood. The learner group, consisting of 21 L1 Chinese speakers who have been learning to read Arabic for 2 years and 4 months, were compared to the matched group on their performance on a series of cognitive tasks that tap into working memory, processing speed, reasoning, conflict monitoring, and attention. The results showed that the learning group’s performance was significantly better in attention (measured by the Posner cueing attention task). Their working memory capacities (measured by the digit span tests) were also better, but the difference only reached marginal significance. The findings suggest that language learning may lead to improvement in attention abilities, which is in line with the converging evidence in the field of bilingualism showing that executive attention may underlie the mechanism of how bilingual experience can alter brain and the cognitive system.